Identification, characterization, and expression of Oryza sativa tryptophan decarboxylase genes associated with fluroxypyr‐meptyl metabolism - Hao Wen Wang; Xu Zhen Shi; Xiao Yu Zhong; Gan Ai; Yan Hui Wang; Zhi Zhong Zhou; Dan Lu; Xiao Liang Liu; Zhao Jie Chen (The Plant Genome)
Abstract Tryptophan decarboxylase (TDC) belongs to a family of aromatic amino acid decarboxylases and catalyzes the conversion of tryptophan to tryptamine. It is the enzyme involved in the first step of melatonin (MT) biosynthesis and mediates several key functions in abiotic stress tolerance. In Oryza sativa under pesticide‐induced stress, TDC function is unclear. Three TDC differentially expressed genes (DEGs) and six TDC‐coding genes were found to be expressed in fluroxypyr‐meptyl (FLUME)‐treated rice transcriptome datasets, which allowed researchers to explore the properties and roles of rice TDC family genes under pesticide‐induced stress. By applying sequence alignment and phylogenetic analysis, two subfamilies of the TDC gene family—DUF674 and AAT_I—were found in rice, Glycine max, Zea mays, Hordeum vulgare, and Solanum lycopersicum. According to chromosomal location studies, segmental duplication aided in the expansion of the OsTDC gene family, and the three TDC DEGs in rice were irregularly distributed on two of its 12 chromosomes. In addition, nine rice TDC genes displayed a collinear relationship with those of soybean, maize, barley, and tomato. Rice TDC genes can encode a variety of biotic and abiotic stress responses because of their diverse gene architectures, cis‐elements, motif compositions, and conserved domains. Reverse transcription‐quantitative polymerase chain reaction (RT‐qPCR) analysis confirmed that a proportion of TDC genes (Os08g0140300, Os08g0140500, and Os10g0380800) were preferably expressed under 0.08 mg L−1 FLUME stress, with a 5.2‐, 3.2‐, and 3.9‐fold increase in roots and a 2.1‐, 2.4‐, and 2.6‐fold increase in shoots, respectively. MT treatment further increased the expression of these genes, with a 2.1‐fold, 3.1‐fold, and fivefold increase in roots and a 1.5‐, 1.1‐, and 1.1‐fold increase in shoots than that treated with 0.08 mg L−1 FLUME only, respectively. When rice seedling roots and shoots were subjected to 0.08 mg L−1 FLUME stress, TDC activity was increased by 2.7 and 1.6 times higher than in the control, respectively. MT application also further promoted TDC activity in rice tissues; TDC activity in rice roots and shoots was twofold and 1.4‐fold higher, respectively, than that under 0.08 mg L−1 FLUME alone. These findings indicate that TDC genes respond effectively to FLUME stress, and the application of MT could enhance the expression of these TDC genes, which comprise a set of candidate genes that regulate pesticide metabolism and degradation with the application of MT.